Evidence and effects of the sunrise enhancement of the equatorial vertical plasma drift in the F region ionosphere - Zhang, Ruilong (2016)
Recent studies based on the satellite observations demonstrated that the equatorial vertical plasma drift can also enhance near sunrise in a way similar to the prereversal enhancement. However, it is not clear whether the signature of this sunrise enhancement appears in observations with other sounding techniques. In this work, we explore the Jicamarca (12°S, 283.2°E) incoherent scatter radar measurements to present the evidence of sunrise enhancement in vertical plasma drift on 12 May and 10 June 2004, which are under magnetically quiet and solar minimum conditions. The effects of the sunrise enhancement on the ionosphere are, for the first time, investigated by analyzing the ionograms recorded by the Digisonde Portable Sounder at Jicamarca and conducting the Theoretical Ionospheric Model of the Earth in Institute of Geology and Geophysics, Chinese Academy of Sciences. The observations showed that, during the sunrise enhancement, the F2 layer peak height is lifted remarkably, and the F2 layer peak density and bottomside electron density tend to decrease compared to the days without sunrise enhancements. The simulations indicated that the sunrise enhancement drift can lift the equatorial ionosphere to higher heights and distort the equatorial electron density profiles. What is more, the simulations display an F3 layer in the equatorial F region during the sunrise enhancement, and a new F2 layer develops at lower altitudes under the jointed control of the usual photochemical and dynamical processes.